AN INTERNATIONAL LAW PRINCIPLE OF NON-REGRESSION FROM ENVIRONMENTAL PROTECTIONS. Issue 1 (January 2023) - Mitchell, Andrew D; Munro, James
Abstract: A principle that prohibits States from weakening their domestic levels of environmental protection continues to emerge at varying speeds within international trade, investment and environmental law. This article explores the principle's diverse history, rationale and legal expression in each of these domains and finds that its various articulations in different international treaties suffer the same shortfalls and deficiencies. Non-regression clauses may leave the complexities and nuances of implementing environmental protections unaddressed, including identifying and measuring when a regression has occurred and balancing these environmental protections with other legitimate policy and environmental measures. As these clauses are increasingly subject to investor–State and State–State dispute procedures, States expose themselves to heightened liability for changes to their environmental laws, even where those changes might be legitimate and reasonable. The particular emergence of this principle in environmental law offers treaty-makers an opportunity to clarify the rights of States to derogate from otherwise narrowly drafted clauses that require them to maintain their level of environmental protection strictly.